2006
DOI: 10.1128/jb.188.3.1205-1210.2006
|View full text |Cite
|
Sign up to set email alerts
|

TheVibrio harveyiGTPase CgtAVIs Essential and Is Associated with the 50S Ribosomal Subunit

Abstract: It was previously reported that unlike the other obg/cgtA GTPases, the Vibrio harveyi cgtA V is not essential. Here we show that cgtA V was not disrupted in these studies and is, in fact, essential for viability. Depletion of CgtA V did not result in cell elongation. CgtA V is associated with the large ribosomal particle. In light of our results, we predict that the V. harveyi CgtA V protein plays a similar essential role to that seen for Obg/CgtA proteins in other bacteria.All living organisms express one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…It has also been reported that the E. coli Obg protein is involved in monitoring DNA damage during DNA replication (22). In contrast, CgtA in V. harveyi does not affect does not affect chromosome segregation (17). In V. cholerae, CgtA-depletion does not cause cell elongation, and no chromosomal defects were observed when nucleoids were visualized with DAPI staining (data not shown).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…It has also been reported that the E. coli Obg protein is involved in monitoring DNA damage during DNA replication (22). In contrast, CgtA in V. harveyi does not affect does not affect chromosome segregation (17). In V. cholerae, CgtA-depletion does not cause cell elongation, and no chromosomal defects were observed when nucleoids were visualized with DAPI staining (data not shown).…”
Section: Resultsmentioning
confidence: 83%
“…This is probably a conserved function because in other organisms, such as V. harveyi, B. subtilis, C. crescentus, and E. coli, CgtA interacts with the 50S ribosomal subunit and has been shown to be involved in assembly or stability of the 50S subunit (17,23,27,28). Interestingly, a yeast mitochondrial CgtA homolog is essential for translation, likely through an involvement in ribosome biogenesis (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of Obg orthologues have examined different temperature-sensitive alleles and point mutations to deplete functional Obg in Gram-negative bacteria (Kobayashi et al, 2001;Datta et al, 2004;Sato et al, 2005;Sikora et al, 2006). The results of these studies have suggested various and diverse cellular roles, including ribosome biogenesis, stress response and chromosome segregation.…”
Section: Obge Is Necessary For Efficient Chromosome Partitioningmentioning
confidence: 99%
“…Genetics studies have also revealed a growth-essential role for the Obg orthologs of Escherichia coli, Caulobacter crescentus, and Vibrio and Streptomyces species (25,34,35,39,43). In vitro, purified B. subtilis and C. crescentus Obgs display high GTP/GDP dissociation exchange rates (K d , ϳ1.5 s Ϫ1 ) but relatively low GTP hydrolysis rates (half-life, ϳ23 min) (32,52).…”
mentioning
confidence: 99%